Analysing Famine: The Politics of Information and Analysis in Food Security Crises. (8th July 2021) - Maxwell, Daniel; Hailey, Peter
Abstract : Famine means destitution, increased severe malnutrition, disease, excess death and the breakdown of institutions and social norms. Politically, it means a failure of governance – a failure to provide the most basic of protections. Because of both its human and political meanings, 'famine' can be a shocking term. This is turn makes the analysis – and especially declaration – of famine a very sensitive subject. This paper synthesises the findings from six case studies of the analysis of extreme food insecurity and famine to identify the political constraints to data collection and analysis, the ways in which these are manifested, and emergent good practice to manage these influences. The politics of information and analysis are the most fraught where technical capacity and data quality are the weakest. Politics will not be eradicated from analysis but can and must be better managed.